Differences in health-related quality of life between the Roma community and the general population in Romania - Tomos Robinson; Yemi Oluboyede; Luke Vale; Elena Olariu (SpringerOpen, 2022)
Abstract Background Previous research has shown that Roma people report worse health outcomes than the general population and suffer from a myriad of economic and social disadvantages. The objective of this study was to assess the differences in the health-related quality of life (HRQoL) between the Roma people and the Romanian general population. Methods Two cross-sectional surveys were conducted face-to-face in 2018 and 2019 in two nationally representative samples of both the general population and Roma communities, recruited from all regions of Romania. Both samples completed the EQ-5D-5L and EQ-VAS questionnaires, as well as a range of sociodemographic questions. Coarsened Exact Matching and several different regression models were used to assess the differences in HRQoL between the two groups. Results 2308 respondents were included in the matched sample: 1,621 general population individuals; 687 Roma people. Roma people had more problems with self-care, pain/discomfort, and anxiety/depression than the general population. They also reported a lower overall level of HRQoL than the general population of Romania, as reflected by the lower EQ-5D-5L and EQ-VAS scores. Our sensitivity analysis between Coarsened Exact Matching and other matching procedures showed consistent results across all regression models. Conclusions In Romania, the Roma community has a lower level of HRQoL than the general population. Understanding the underlying causes of this inequality should be the focus of future research. Policies aimed at reducing the level of health inequality between the Roma and the general populations should be promoted locally.